Improving Outcomes: A Retrospective Review Study Design in Pathology Education for Medical Students. Issue 6 (8th August 2019) - McBrien, Sarah; Bailey, Zachary; Ryder, Jonathan; Scholer, Paige; Talmon, Geoffrey
Abstract: Objectives: To determine the strength of study design and outcomes in literature describing pathology education for medical students. Methods: A search was conducted for articles related to pathology education published over 45 years describing an educational intervention. The primary data collected included phase of education, domain of objectives, number of learners and institutions, type of intervention, use of a comparison/control group, randomization, and strength of statistical analysis. Results: Of 655 articles, 54 (8%) met inclusion criteria. The majority (65%) reported experiences of 100 learners or fewer, and only one was multi-institutional. Only 46% used a comparison/control group. Statistical significance of results was not reported in 39%. None examined outcomes at a point distant from the educational intervention. Conclusions: Most studies describing pathology educational interventions are not of strong experimental design. Consumers of educational research should be cognizant of these potential weaknesses in educational studies.